Anthropometric measures that identify premature and low birth weight newborns in Ethiopia: a cross-sectional study with community follow-up. Issue 4 (1st November 2019) - Gidi, Netsanet Workneh; Berhane, Melkamu; Girma, Tsinuel; Abdissa, Alemseged; Lim, Ruth; Lee, Katherine; Nguyen, Cattram; Russell, Fiona
Abstract : Objective: To investigate foot length (FL), chest circumference (CHC) and mid-upper arm circumference (MUAC) as predictors of low birth weight (LBW) or prematurity, and to describe the agreement between the gestational age (GA) assessments ascertained by the New Ballard Score (NBS) and the Eregie model. Methods: A hospital-based cross-sectional study with community follow-up in a subset was conducted in Jimma University Medical Center, Ethiopia. GA (NBS and Eregie model), weight, FL, CHC and MUAC were measured at birth. Anthropometrics were repeated at 5 days of age. Results: The optimal cut-offs indicative of LBW were ≤7.7 cm for FL; ≤31.2 cm for CHC and ≤9.8 cm for MUAC. CHC, MUAC and FL identified LBW with sensitivities (95% CI) of 91.6 (86.9 to 95), 83.7 (77.8 to 88.5) and 84.2 (78.4 to 88.9), and specificities (95% CI) of 85.4 (83.3 to 87.4), 90.2 (88.4 to 91.9) and 73.9 (71.3 to 76.4), respectively. CHC, MUAC and FL identified prematurity with sensitivities of 83.8 (76.7 to 89.4), 83.1 (75.9 to 88.9) and 81.7 (74.3 to 87.7), and specificities of 81.1 (78.9 to 83.3), 63.4 (60.7 to 66.1) and 77.0 (74.6 to 79.3), respectively. The cut-offs identified have comparable diagnostic ability for LBW and prematurity when measurements are repeated on day 5 of age. The GA assessment by the NBS and the Eregie model gave similar results, with the mean difference of 1.2 weeks. Conclusion: CHC, MUAC and FL taken on day 1 and 5 after birth could be used as diagnostic tools for LBW or prematurity. The Eregie model for GA estimation gives similar results to the NBS.